1998
DOI: 10.1038/ng0598-25
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for Prader-Willi syndrome imprinting-centre mutations

Abstract: Imprinting in the 15q11-q13 region involves an 'imprinting centre' (IC), mapping in part to the promoter and first exon of SNRPN. Deletion of this IC abolishes local paternally derived gene expression and results in Prader-Willi syndrome (PWS). We have created two deletion mutations in mice to understand PWS and the mechanism of this IC. Mice harbouring an intragenic deletion in Snrpn are phenotypically normal, suggesting that mutations of SNRPN are not sufficient to induce PWS. Mice with a larger deletion inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
207
1
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(213 citation statements)
references
References 38 publications
3
207
1
2
Order By: Relevance
“…The alternative promoter for the IC transcript might be used to express Snurf-Snrpn. However, previous analysis of a knockout mouse experiment (Yang et al 1998) demonstrated that, unlike the Dnmt1o protein, the Snurf-Snrpn protein is not essential for normal mouse development. Therefore, the role of the IC transcript may be different from that of the alternative transcript of the Dnmt1 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative promoter for the IC transcript might be used to express Snurf-Snrpn. However, previous analysis of a knockout mouse experiment (Yang et al 1998) demonstrated that, unlike the Dnmt1o protein, the Snurf-Snrpn protein is not essential for normal mouse development. Therefore, the role of the IC transcript may be different from that of the alternative transcript of the Dnmt1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…1a) for deletions among such PWS patients, spans less than 4.3 kb and includes exon 1 of the SNURF-SNRPN (SNRPN upstream reading frame-small nuclear ribonucleoprotein polypeptide N) gene (Ohta et al 1999). The mouse PWS-SRO ortholog is also located at the upstream region of Snurf-Snrpn (Yang et al 1998;Fig. 1b), and functions to maintain the paternal epigenotype in the mouse PWS/ AS imprinting domain in somatic cells (Bielinska et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…93 Unfortunately, mouse models for the multigene deletion associated with PWS have shown early postnatal lethality. 94,95 Other mouse lines have been developed with more specific targeted disruptions, focusing on the expression of a single gene from the imprinted region, Necdin (Ndn). In one study, the majority of mice with paternal inheritance of a Ndn null allele died, most likely of respiratory depression, within hours of birth.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 99%
“…Electrocorticographic (ECoG) recordings on paternally duplicated mice showed a striking diffuse cortical excitability disturbance that was identical in all animals. However, mice harboring an intragenic deletion in Snrpn are phenotypically normal (Yang et al, 1998) suggesting that mutations of Snrpn are not sufficient to produce the PWS phenotype. Mice with larger deletion, including both Snrpn and the putative PWS-IC (PWS-imprinting center), lack expression of the imprinted genes Zfp127, Ndn and Ipw, and manifest several phenotypes of PWS patients (Yang et al, 1998).…”
Section: Prader-willi / Angelman Syndromementioning
confidence: 99%
“…Snrpn and imprinting center targeted mutagenesis (Yang et al, 1998); Ndn targeted mutagenesis (Muscatelli et al, 2000); uniparental disomy (Cattanach et al, 1992); transgene-induced deletion (Gabriel et al, 1999) (Jiang et al, 1998); uniparental disomy (Cattanach et al, 1997); transgene-induced deletion (Gabriel et al, 1999) Tuberous sclerosis-2 (TSC2) del (16) Lis1 targeted mutagenesis (Hirotsune et al, 1998) and hypomorph (Cahana et al, 2001);14-3-3- …”
mentioning
confidence: 99%